The integration challenge in Canadian regionalization - Gregory Marchildon
In the 1990s, regionalization was introduced in Canada through administrative delegation in order to achieve a number of reform objectives, but among the most important was to improve the integration of services across diverse health sectors. Despite the failure of regionalization in fulfilling its promise of integration, regionalization still provides a foundation for achieving system-wide integration. For this to occur, however, regional and provincial health authorities need to be given the effective accountability for primary care. Given that primary healthcare physicians provide the majority of primary care in Canada, the funding for primary care physicians should be returned from provincial ministries of health to regional (or provincial) authorities in order to allow them the opportunity to become responsible for coordinating health services for their patient populations across the continuum of care, and to contract providers with the necessary incentives and penalties.